2018
DOI: 10.1016/j.ijscr.2018.03.039
|View full text |Cite
|
Sign up to set email alerts
|

A case of retroperitoneal desmoid-type fibromatosis that involved the unilateral ureter after gynaecologic surgery

Abstract: HighlightsThere are little reports of postoperative intra-abdominal desmoid-type fibromatosis.This case involved a unilateral ureter after gynaecologic surgery.Diagnosing the extent of tumour invasion via preoperative imaging is difficult.It may be necessary to examine the urinary tract before the operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Actually, a recent review paper by The Desmoid Tumor Working Group found no documented evidence to support the use of antihormonal therapies or NSAIDs in patients with DF 4 . Regarding tranilast, which has long been considered effective in DF in Japan, it was not taken up in the aforementioned review paper because no case series have been reported, and only 2 cases were previously reported in PubMed 26,27 . If the drug can indeed change the “natural course” of DF preoperatively, it would make sense to carry out surgery in the stable or regression phase, thereby reducing the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a recent review paper by The Desmoid Tumor Working Group found no documented evidence to support the use of antihormonal therapies or NSAIDs in patients with DF 4 . Regarding tranilast, which has long been considered effective in DF in Japan, it was not taken up in the aforementioned review paper because no case series have been reported, and only 2 cases were previously reported in PubMed 26,27 . If the drug can indeed change the “natural course” of DF preoperatively, it would make sense to carry out surgery in the stable or regression phase, thereby reducing the recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…4 Regarding tranilast, which has long been considered effective in DF in Japan, it was not taken up in the aforementioned review paper because no case series have been reported, and only 2 cases were previously reported in PubMed. 26,27 If the drug can indeed change the "natural course" of DF preoperatively, it would make sense to carry out surgery in the stable or regression phase, thereby reducing the recurrence rate. In the present study, only 1 patient who remained recurrence-free after surgery had received low-dose MTX + VBL therapy.…”
Section: Discussionmentioning
confidence: 99%
“…According to available literature, aggressive fibromatosis is a rare tumor of monoclonal fibroblastic proliferation, which is characterized by variable and complicated clinical processes [3, 4], These are divided into three categories depending on their anatomical location: extra-abdominal (60%), abdominal wall (25%), and intra-abdominal (8–15%) [9]. The Intra-abdominal AF often occurs in the small intestinal mesentery, but it can also occur in the posterior peritoneum, ileocolic mesentery, gastrocolic ligament and greater omentum.…”
Section: Discussionmentioning
confidence: 99%
“…Some present as surgical emergencies with bleeding requiring emergency laparotomy . Fibromatosis has also been reported after abdominal surgery for benign tumours, such as uterine myoma , or mimicking recurrent GIST either in the mesentery or the retroperitoneum .…”
Section: Discussionmentioning
confidence: 99%